Predictors of Short- and Long-Term Mortality in Ischemic Stroke: A Community-Based Study in Brno, Czech Republic - Bryndziar, Tomas; Matyskova, Dominika; Sedova, Petra; Belaskova, Silvie; Zvolsky, Miroslav; Bednarik, Josef; Brown, Robert D; Mikulik, Robert (Cerebrovascular diseases (Basel, Switzerland), 2022)
BACKGROUND AND OBJECTIVE: Short- and long-term mortality following ischemic stroke (IS) and their predictors have not been defined in the Czech population, and studies on long-term mortality are largely missing for the populations of Central Europe. METHODS: Using the National Register of Hospitalized Patients and the Czech National Mortality Registry, we analyzed data on 1-month, 1-year, and 3-year all-cause mortality for patients admitted with IS to any of the 4 hospitals with a certified stroke unit in Brno, Czech Republic, in 2011. We reviewed discharge summaries and recorded potential factors impacting mortality after the index stroke event. Using univariate and multivariable analyses, we identified predictors of mortality at all 3 time points. RESULTS: In our multivariable model, statin use (odds ratio [OR] 0.095, p < 0.0001), age at stroke (OR 1.03, p = 0.0445), and admission National Institutes of Health Stroke Scale (NIHSS) score (OR 1.16, p < 0.0001) predicted 1-month mortality, while statin use (OR 0.43, p = 0.0004), history of cardiac failure (OR 2.17, p = 0.0137), age at stroke (OR 1.07, p < 0.0001), and admission NIHSS score (OR 1.14, p < 0.0001) predicted 1-year mortality. Statin use (OR 0.54, p = 0.0051), history of cardiac failure (OR 2.13, p = 0.0206), age at stroke (OR 1.07, p < 0.0001), and admission NIHSS score (OR 1.11, p < 0.0001) also predicted 3-year mortality. CONCLUSIONS: Our study is the first to report data on short- and long-term mortality rates and their predictors in patients hospitalized with IS in the Czech population. Our results indicate that mortality rates and predictors of mortality are consistent with those reported in studies from other populations throughout the world.
Keywords: ischemie mozku; statiny; Brain Ischemia; Humans; Heart Failure; srdeční selhání; Stroke; Hydroxymethylglutaryl-CoA Reductase Inhibitors; rizikové faktory; lidé; Mortality; Ischemic Stroke; cévní mozková příhoda; stupeň závažnosti nemoci; Retrospective Studies; Czech Republic; ischemická cévní mozková příhoda; Severity of Illness Index; retrospektivní studie; Česká republika; Ischemic stroke; Risk Factors